A Qualitative Study Exploring Factors Associated with Retention in HIV Care among Women with HIV in a Large HIV Clinic in Lagos, Nigeria, after Implementing the Test and Treat Policy. (9th August 2022) - Odediran, Omoladun O.; Odukoya, Oluwakemi O.; Balogun, Mobolanle R.; Colasanti, Jonathan A.; Akanmu, Alani S.
Abstract : Background . In Nigeria, various sociocultural and economic factors may prevent women from being retained in HIV care. This study explores the factors associated with retention in care among women with HIV in a large HIV clinic in Lagos, Nigeria, under the Test and Treat policy. Methods . Women living with HIV/AIDS ( n  = 24) enrolled in an HIV study at the AIDS Prevention Initiative in Nigeria (APIN) clinic in Lagos, Nigeria, were interviewed from April 1 to October 31, 2021, using a semistructured interview guide. Interviews were audio-taped, transcribed verbatim, and the themes were analyzed using the framework of Andersen and Newman's Behavioural Model for Healthcare Utilization. Results . The mean age of the respondents was 37.4 ± 9.27 years. The identified themes were as follows: being aware of the antiretroviral medications and their benefits, the household's awareness of the respondents' HIV status, and the presence of social support. Other themes were the presence of a dependable source of income and the ability to overcome the challenges encountered in obtaining income, ease of travel to and from the clinic (length of travel time and transportation costs), securing support from the clinic, challenges encountered in the process of accessing care at the clinic, and the ability to overcome these challenges. Also mentioned were self-perception of being HIV positive, motivation to remain in care, linkage to care, and intention to stay in care. Conclusion . Several deterring factors to retention in HIV care, such as nondisclosure of status, absence of social support, and clinic barriers, persist under the Test and Treat policy. Therefore, to achieve the "treatment as prevention" for HIV/AIDS, especially in sub-Saharan Africa, it is essential to employ strategies that address these barriers and leverage the facilitators for better health outcomes among women with HIV/AIDS.